Income and electricity consumption issue: evidence from European households - Nguyen, Ngoc Dat; Nguyen, Duy Van; Dao, Kien Trung; Than, Thuy Trong; Nguyen, Dat Dinh (Journal of International Economics and Management, 2024)
Research on electricity consumption plays an important role in the development of sustainable national strategies and mitigation of global climate change. With global economic development in general, and Europe in particular, the demand for electricity in households is increasing. Therefore, based on demand theory, this study evaluates the impact of income on electricity consumption in European households. Data were collected from 35 European countries and analyzed. The instrumental variable regression results indicate that income positively impacts electricity consumption in European households. The electricity consumption of European households provides evidence that supports the prediction of demand theory, as an increase in household income as well as a decrease in price leads to a rise in overall consumption. However, the effect of price is not statistically significant. The findings also show that population growth and inflation positively influence household electricity consumption. The outcomes of this study have theoretical and practical implications for improving energy efficiency and effective electricity use in European households. Therefore, it is necessary to continue implementing energy-saving strategies at the household level in the context of increasing electricity consumption in Europe.